Determinants of compliance to occupational health and safety measures in construction sites in Kampala Central Division, Kampala city, Uganda - Naluwemba Mayanja, Lillian; Ddamulira, Christopher; Katamba, Paul; Mutekanga, David R. (World journal of advanced research and reviews, 2022)
The study examined the determinants of compliance to safety and health measures in construction sites in Kampala Central Division, Uganda. Questionnaires containing information relating to safety and health measures at the sites were administered randomly to the construction workers selected from four (4) selected building sites across the division. The results revealed that there was a 95% level of compliance to safety and health measures which is considered an unacceptable standard and requires attention in the short term according to the scale developed by MBSAT, among the building construction workers in the division. It was also established that there were no personal determinants that affected compliance to safety and health measures within the division as all of them were found to be statistically insignificant. This indicated that none of the personal determinants is a significant predictor of compliance (at 5% level of significance). The results further revealed that there was a significant association between three organizational determinants of compliance: adequacy of legislation, availability of personal protective equipment (PPE) and availability of standard operating procedures (SOPs) or policy. This proved that there is an association between personal and organizational determinants of compliance to occupational safety in construction sites in Kampala Central Division (at 5% level of significance). However in practice this means there is no one single factor which can determine compliance but a combination of factors of which the organizational factors are more significant in compliance than personal determinants.
Keywords: Determinants; Compliance; Construction Workers; Safety and Health Measures